1977
DOI: 10.1007/bf00390430
|View full text |Cite
|
Sign up to set email alerts
|

Preferential derivation of abnormal human G-group-like chromosomes from chromosome 15

Abstract: The marked binding of antibodies specific for 5-methylcytidine to the short arm of chromosome 15 distinguishes this chromosome from the other human acrocentrics. This method has been used to study over 60 individuals including 12 who did not have Down's syndrome, but who did have an extra G-group sized acrocentric chromosome. In six cases the extra chromosome did not show intensive binding of anti-5-methylcytidine. In the other six cases, the extra chromosome contained a 5-methylcytidine rich band at each end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0
2

Year Published

1980
1980
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(64 citation statements)
references
References 15 publications
4
58
0
2
Order By: Relevance
“…33 Both groups of SMC(15)s were also shown to have asymmetrical breakpoints and, furthermore, the two main breakpoint regions occur at sites of duplicated genomic segments, 34 suggesting that these duplicons are responsible, at least in part, for the increased instability in this region, and the most popular theory for the formation of SMC (15)s is a U-type exchange between homologous chromosomes during meiosis I followed by illegitimate fusion of the chromatids and nondisjunction. 35,36 A combination of these events, with maternal age related nondisjunction as the primary mechanism, may go some way to explain the relatively high frequency with which SMC(15)s are ascertained in the human population.…”
Section: Parental Age Effects In Smcsmentioning
confidence: 99%
“…33 Both groups of SMC(15)s were also shown to have asymmetrical breakpoints and, furthermore, the two main breakpoint regions occur at sites of duplicated genomic segments, 34 suggesting that these duplicons are responsible, at least in part, for the increased instability in this region, and the most popular theory for the formation of SMC (15)s is a U-type exchange between homologous chromosomes during meiosis I followed by illegitimate fusion of the chromatids and nondisjunction. 35,36 A combination of these events, with maternal age related nondisjunction as the primary mechanism, may go some way to explain the relatively high frequency with which SMC(15)s are ascertained in the human population.…”
Section: Parental Age Effects In Smcsmentioning
confidence: 99%
“…Miller et al (1977) have shown a strong correlation between the amount of silver stain and frequency of participation in association. In the cases reported here, the marker chromosome carried an above-average number of l8S and 28S ribosomal genes and was involved more often than average in satellite associations.…”
Section: Resultsmentioning
confidence: 93%
“…Studies on rodent/man somatic cell hybrids have shown that only the NOR's of the species producing rRNA are stained by the Ag technique (Miller et al, 1977), and it has been assumed that this is a stain for active NOR's. Satellite association has also been considered as a measure of activity in production of rRNA as it is thought to involve those acrocentric chromosomes whose NOR's were involved in nucleolus formation in the previous interphase.…”
Section: Resultsmentioning
confidence: 99%
“…9 To the best of our knowledge, a 22q11 duplication together with a deletion in the same patient has hitherto never been reported. Inverted duplications have been suggested to arise as a U-type exchange between homologous chromosomes 11,12 or inter-chromosomal recombination between inverted sequences. 6,13 Another alternative is repair of a broken chromosome through replication and end to end fusion.…”
Section: Discussionmentioning
confidence: 99%
“…6,13 Another alternative is repair of a broken chromosome through replication and end to end fusion. 11 We hypothesize that an inter-chromosomal recombination between inverted repeats combined with a recombination between sister chromatids during meiosis I gave rise to both a deleted 22q11 and an inv dup(22) containing the DGS region (Figure 2). The acentric fragments were lost.…”
Section: Discussionmentioning
confidence: 99%